B C Almanac (H) C-B : The National Film Board of Canada - Image 8. (Vancouver : The National Film Board of Canada, 1970)
Dale, Jack ; deCoucry, Michael ; Dikeakos, Christos ; Englinton, Judtih ; Gilbert, Gerry ; Kiyooka, Roy ; Lewis, Glen ; Masciuch, Taras ; Morris, Michael ; N.E. Thing Co. Ltd. ; Pane, Jone ; Porter, Timothy ; Thomas, Peter ; Trasov, Vincent ; Wood, Robertson. Each made a book
This photographic book is one of a set of fifteen volumes (480 pages) produced by the National Film Board of Canada exhibition B C Almanac(H) C-B, 1970
Text French-English
kunstcatalogus
Keywords: Canada